CONTINUITY OF CARE IN NY. S AGE 34 YEARS OLD WITH MILD ANEMIA DIPMB HAMIDAH, KEC. MEDAN MAIMUN, MEDAN CITY, NORTH SUMATRA IN 2025 - Harahap, Yesica Romayan; Siti Nurmawan Sinaga; Hamidah; Elisa Cibro; Nurul Umaira; Intan Nazira; Nurazizah (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Anemia is a condition in which the number of red blood cells (erythrocytes) or the level of hemoglobin (Hb) in the blood is insufficient for the body’s physiological needs. This study focuses on the relationship between education level and anemia cases in pregnant women. The main cause of anemia is due to pregnant women lacking iron intake, vit D, vit B12, lack of blood cells. (Saras, 2023) This case study describes the treatment of anemia in a 34-year-old pregnant woman with a gestation of 38 weeks and 5 days. The care provided includes the provision of FE tablets and providing nutritious food-related kie and encouraging frequent visits to ANC The purpose of this service is to increase the understanding of pregnant women about the prevention and treatment of anemia in the research area at Pmb Hamidah. ( Squirt & Lestarini , 2024) The method used in this service is education and the administration of Fe tablets. The results of this activity showed an increase in pregnant women’s knowledge about anemia and how to prevent anemia. In conclusion, education and intervention in administering Fe tablets in handling cases in this region.(WHO, 2023)